2017
DOI: 10.1111/anu.12466
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive evaluation of replacing fishmeal with housefly (Musca domestica ) maggot meal in the diet of Nile tilapia (Oreochromis niloticus ): growth performance, flesh quality, innate immunity and water environment

Abstract: A 10‐week feeding trial of using housefly (Musca domestica) maggot meal (MM) in practical feeds for Nile tilapia (Oreochromis niloticus) was conducted to assess the growth performance, ingredient utilization, flesh quality, innate immunity and its influence on water environment. Fish were fed five isonitrogenous and isoenergetic diets, where fishmeal (FM) was substituted by MM at the level of 0, 90, 180, 270 and 360 g kg‐1 diet (remaining FM content: 360, 270, 180, 90 and 0 g kg‐1). There was no significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 41 publications
7
32
0
Order By: Relevance
“…The ADC of dry matter may be affected by the type of raw material employed for rearing of insect larvae. A similar result was obtained when substituting FM with housefly (Musca domestica) maggot meal in the diet of O. niloticus fingerling (Ogunji et al, 2007;Wang et al, 2017). The lower ADC for crude protein of DFSM may be due to lower content in some essential amino acids like methionine (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…The ADC of dry matter may be affected by the type of raw material employed for rearing of insect larvae. A similar result was obtained when substituting FM with housefly (Musca domestica) maggot meal in the diet of O. niloticus fingerling (Ogunji et al, 2007;Wang et al, 2017). The lower ADC for crude protein of DFSM may be due to lower content in some essential amino acids like methionine (Table 2).…”
Section: Discussionsupporting
confidence: 60%
“…This higher P digestibility resulted in a pronounced reduction of total P losses, which suggests that the use of dTM as a FM replacer in European sea bass could help reducing P output into the environment. Likewise, Wang et al (2017) demonstrated in Nile tilapia that FM replacement by increasing levels of M. domestica from 18% to 100% resulted in lower concentrations of total phosphate in the water. This metabolic feature might be part of the adaptive response of fish facing a reduced dietary P supply.…”
Section: Discussionmentioning
confidence: 96%
“…This was supported by the lack of changes in skeletal muscle cellularity and instrumental texture properties. To our best knowledge, the muscle cellularity of fish fed IM diets was never assessed before, but previous studies in different farmed fish species have evidenced the preservation of textural properties with high levels of FM replacement by IM (Lock et al, 2016;Borgogno et al, 2017;Iaconisi et al, 2017;Wang et al, 2017;Secci et al, 2019;Bruni et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Smallholder farms in Asia and Africa commonly use insects as fish feed (Dobermann et al, 2017). Housefly-larvae meal can replace up to 75% of fishmeal in Nile tilapia diets without any adverse effects (Wang et al, 2017). Replacing fish meal with black-soldier-fly meal in diets does not alter the odor, flavor, or texture of Atlantic salmon ( Salmo salar ) (Lock et al, 2016).…”
Section: Industrial Applications Of Insects As Food and Feed Sourcesmentioning
confidence: 99%